2012
DOI: 10.1002/jbt.21465
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter Containing Environmentally Persistent Free Radicals and Adverse Infant Respiratory Health Effects: A Review

Abstract: The health impacts of airborne particulate matter (PM) are of global concern, and the direct implications to the development/exacerbation of lung disease are immediately obvious. Most studies to date have sought to understand mechanisms associated with PM exposure in adults/adult animal models; however, infants are also at significant risk for exposure. Infants are affected differently than adults due to drastic immaturities, both physiologically and immunologically, and it is becoming apparent that they repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(77 citation statements)
references
References 116 publications
(127 reference statements)
1
76
0
Order By: Relevance
“…EPFRs are a risk to human health through both acute 2,8–12 and chronic exposure. 11,13 Further, they are intermediates in the formation of polychlorinated dibenzo- p -dioxins and polychlorinated furans (PCDD/F).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPFRs are a risk to human health through both acute 2,8–12 and chronic exposure. 11,13 Further, they are intermediates in the formation of polychlorinated dibenzo- p -dioxins and polychlorinated furans (PCDD/F).…”
Section: Introductionmentioning
confidence: 99%
“…The overproduction of ROS results in oxidative stress increasing susceptibility to respiratory and cardiovascular diseases. 1,4,12,13,16–21 The condensation reactions that EPFRs undergo to form PCDD/Fs constitute another significant environmental and health risk that calls for EPFR prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies investigating the impact of particulate matter on the human population have shown a negative correlation between the amount of PM in air and human health (Jędrychowski et al, 2011;Weuve, 2012;Saravia et al, 2013;Hsu et al, 2015). It has been estimated that exposure to PM causes approximately 2.1 million premature deaths annually worldwide, associated with cardiopulmonary diseases and lung cancer (Silva et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their ability to deposit deep in the lower airways, the smaller classes of PM are more apt to cause respiratory toxicity and dysfunction. Furthermore, various chemical compounds bound to these small particles, such as PAHs, may eventually enhance (or at least contribute to) the PM-induced adverse health effects (Kim et al, 2013;Saravia et al, 2013 (IARC, 2002(IARC, , 2010. The mean concentrations of these 10 carcinogenic PAHs (i.e., Σ PAHscarc ) in indoor PM, gas-phase, and in indoor air are reported also in Table 2.…”
Section: Outdoor Pahs and Source Identificationmentioning
confidence: 99%